2019
DOI: 10.1016/j.measurement.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Laser diodes optical output power model

Abstract: This article proposes a modelling method of laser diodes optical output power, especially for mid-high power diodes working in continuous wave (CW) or quasi continuous wave (QCW) modes, and focusing in the optical output power dependency on temperature and its model implementation in Pspice, targeting its computer simulation. It is commented the theory and related mathematical expressions used in the model, the Pspice program model and the purpose of its different parts, and how mathematical expressions are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In the past, this characteristic has been studied theoretically and experimentally in the broad field of laser diodes to determine the threshold for lasing. [113][114][115] In addition, it also plays an important role in showing properties of laser diodes with and without PR effects. In 1990, Gigase et al reported that the threshold pump power of an AlGaAs-GaAs ridge quantum well laser diode can decrease by PR.…”
Section: Output Power Of Laser Diodesmentioning
confidence: 99%
“…In the past, this characteristic has been studied theoretically and experimentally in the broad field of laser diodes to determine the threshold for lasing. [113][114][115] In addition, it also plays an important role in showing properties of laser diodes with and without PR effects. In 1990, Gigase et al reported that the threshold pump power of an AlGaAs-GaAs ridge quantum well laser diode can decrease by PR.…”
Section: Output Power Of Laser Diodesmentioning
confidence: 99%
“…Authors in [6] reported a diamagnetic spring to act as a radiation pressure meter. Authors in [7] developed a model using Pspice simulation software and a comparison between the model and the actual diode was studied. The same problem of temperature dependence and stabilization in case of high power laser was encountered and studied in [8] in the case of high power diode-pumped Tm: YLF.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, due to the increased integration and packing density of optical modules, they consume more power and generate more heat while providing robust functionalities, thus requiring improved heat dissipation of the modules. [41,42] At the same time, the optical module must be warmed up to the specified operating temperature before it can start up in a low-temperature environment.…”
mentioning
confidence: 99%